Effect of adding biomass fly ash to co-composting of tree pruning waste and cow dung - Somjai Karnchanawong (2018)
The objective of this study was to determine the effect of adding biomass fly ash to cocomposting of tree pruning waste and cow dung. Shredded tree pruning waste and cow dung were used as compost mix. Biomass fly ash was added to achieve the following proportions: 0% (control), 4%, 8% and 12% (wt/wt). The mixtures, turned once a week, were composted in 120-L perforated polyethylene bins for 150 days. The temperature in the middle of the waste layer in each bin was recorded daily, and averaged 32.1-33.3°C. Compost was taken randomly from each bin once a week during turning and its characteristics analysed. The pH of the compost mixes gradually increased from 6.96-8.41 to 8.51-8.95. The EC of the compost mixes increased from 0.69-0.88 dS/cm to 0.97-1.21 dS/cm. The C/N ratio of the compost mixes decreased continuously from around 30 to stability at 12.96-14.04. The volatile solids of the compost mixes decreased continuously from 79.8-87.8% to stability at 55.4-68.5%. The initial NH3-N and NO3-N in the compost mixes were 9.1-11.5 and 1.75-3.03 mg/kg, respectively. The NH3-N contents decreased to 5.41-7.31 mg/kg, while the NO3-N increased to 6.45-7.84 mg/kg. We investigated more than half of the organic portion of each compost mix. Adding fly ash up to 12% (wt/wt) did not affect the composting process or resulting compost, and there was no indication that its high pH increased ammonia volatilization during composting. © (2014) Trans Tech Publications, Switzerland.